Serious China: The rise of China and EU implications - Franklin L. Lavin (European Centre for International Political Economy (ECIPE), 2013)
In a new paper - based on a talk at an ECIPE conference - Ambassador Frank Lavin, former U.S. Undersecretary of Commerce, argues that China now is a consequential nation and will take up a large role in global economic and foreign policy.
Keywords: 330